Delayed entry into HIV care after diagnosis in two specialized care and treatment centres in Cameroon: the influence of CD4 count and WHO staging - Noah F. Takah; George Awungafac; Leopold N. Aminde; Innocent Ali; Juliana Ndasi; Patrick Njukeng (BMC, 2016)
Abstract Background Delayed entry into HIV care has complicated the challenges faced in sub-Saharan Africa due to the high HIV burden. A clear knowledge of the factors affecting delayed entry will be essential in directing interventions towards reducing delayed entry into HIV care. There exist very limited data on delayed entry in Cameroon despite its relevance; hence this study was conducted to determine the rate of delayed entry and its associated factors in HIV programmes in Cameroon. Methods Data used for this study was routine data obtained from the files of HIV patients who were diagnosed between January 1, 2015 and June 30, 2015 at Limbe and Buea regional hospital HIV centers in the South West region of Cameroon. Data analysis was done using SPSS version 20. Results Of the 223 patients included in the study, nearly one-quarter of patients (22.4 %) delayed to enter HIV care within 3 months. Those who delayed to enter care were less likely to present at first diagnosis (using HIV rapid test) with symptoms such as fever > 1 month (5 % versus 30 %, p = 0.01) and weight loss > 10 % (13 % versus 48 %, p < 0.001). Alcohol consumption, WHO stage and CD4 count levels were also associated with delayed entry in bivariate analysis. In multivariate analysis only CD4 count greater than 500cells/μl and WHO stages I and II were independently associated with delayed entry into HIV care within 3 months. Conclusion In the South West region of Cameroon, approximately 1 out of 4 patients delay to enter HIV care. This high proportion of patients who delay to enter care correlates to the findings recorded by other studies in sub Saharan Africa. Interventions tackling delayed entry into HIV care might need to be favorably directed towards patients that have high CD4 counts and are at very early WHO clinical stages.